2013
DOI: 10.1097/acm.0b013e3182a7f071
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Adjustment

Abstract: For more than half a century, scientific research has documented widespread avoidance and even denial of aging. Though nothing new, aversive reactions to the elderly are not only unfortunate but dangerous today, as increasing life expectancy and consequent demand for specialized geriatric medical care vastly outpace the supply of qualified clinicians equipped to provide it. This discrepancy has led to a crisis that is not easily resolved. At the same time, geriatrics reports the highest level of physician sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Similarly, the survey data indicated that attitudes towards working with older adults improved significantly over the course of the clinical placement. The results of this study reinforce mixed international evidence for variable medical student attitudes towards older adults, aged care, and geriatric medicine [ 18 22 , 45 , 52 ]. International research shows that although students may hold negative, neutral or positive attitudes towards older adults prior to clinical engagement, exposure to this cohort as part of medical training can significantly improve attitudes [ 21 , 45 , 53 ].…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, the survey data indicated that attitudes towards working with older adults improved significantly over the course of the clinical placement. The results of this study reinforce mixed international evidence for variable medical student attitudes towards older adults, aged care, and geriatric medicine [ 18 22 , 45 , 52 ]. International research shows that although students may hold negative, neutral or positive attitudes towards older adults prior to clinical engagement, exposure to this cohort as part of medical training can significantly improve attitudes [ 21 , 45 , 53 ].…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, in our study, the clerks’ properties of task achievement goal motivation orientation might drive them to be interested in information relevant to clarifying task demands and promoting mastery [53], thereby buffering the negative effects of physical demands on their burnout to a certain extent. However, regarding the negative effects of training demands (psychological and physical), we observed a limited effect of the task achievement motivation orientation of the medical students only in the 1st year, but not in the 2nd year; therefore, several preventive strategies and preparations must be initiated early, which include clerkship preparation skill courses [54], attitude adjustment [55], and social supports from interpersonal, supervisory, and managerial or organizational stakeholders [56, 57]. …”
Section: Discussionmentioning
confidence: 99%
“…But they lack the time to stop and question, why? [ 3 ] Bensadon et al point to how students' aging-related attitudes negatively impact career and treatment decisions thereby contributing to the deficit of practitioners available to care for people with ADRD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiential learning models, designed to stretch thinking modalities, without increasing time requirements, may sufficiently alter medical trainees attitudes, so they feel more comfortable communicating with and caring for people with ADRD [ 3 , 6 , 9 , 10 ]. Studies support that artistic interventions affect the attitudes of people caring for those with ADRD [ 7 , 9 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%